Resveratrol exerts anti-inflammatory and neuroprotective effects to prevent memory deficits in rats exposed to chronic unpredictable mild stress - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
A number of studies have recently focused on the neuroprotective and anti-inflammatory effects of resveratrol. In prior studies, we described its beneficial effects on scopolamine-induced learning deficits in rats. The aim of this study was to investigate the effects of resveratrol on emotional and spatial cognitive functions, neurotropic factor expression, and plasma levels of proinflammatory cytokines in rats exposed to chronic unpredictable mild stress (CUMS), which is known to induce cognitive deficits. Resveratrol (5 or 20 mg/kg) was administered intraperitoneatly for 35 days. Rats in the CUMS group and in the 5 mg/kg resveratrol + CUMS group performed poorly in tasks designed to assess emotional and spatial learning and memory. The 20 mg/kg resveratrol + CUMS group showed improved performance compared to the CUMS group. In addition, the CUMS procedure induced lower expression of brain-derived neurotrophic factor and c-Fos in hippocampal CA1 and CA3 and in the amygdala of stressed rats. These effects were reversed by chronic administration of resveratrol (20 mg/kg). In addition, plasma levels of tumor necrosis factor-alpha and interleukin-1 beta were increased by CUMS, but were restored to normal by resveratrol. These results indicate that resveratrol significantly attenuates the deficits in emotional learning and spatial memory seen in chronically stressed rats. These effects may be related to resveratrol-mediated changes in neurotrophin factor expression in hippocampus and in levels of proinflammatory cytokines in circulation. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Resveratrol; Chronic mild stress learning; Memory; BDNF; c-Fos; TNF-alpha; IL-1 beta; NITRIC-OXIDE SYNTHASE; NECROSIS-FACTOR-ALPHA; NEUROTROPHIC FACTOR; ACETYLCHOLINESTERASE ACTIVITY; GLUTAMATE NEUROTOXICITY; PREFRONTAL CORTEX; WORKING-MEMORY; ANIMAL-MODELS; MOUSE MODEL; C-FOS